Pengaruh Repositioning, Renaming, Redesign, dan Relaunch Terhadap Keputusan Pembelian Konsumen AZKO - Maulana, David; Nailis, Welly; Putri, Yulia Hamdaini; Yanovi, Ana; Subagja, Ghia (Teewan Journal Solutions, 2026)
This research aims to analyse the influence of repositioning, renaming, redesign, and relaunch on consumer purchasing decisions of AZKO in the city of Palembang. The research uses a quantitative approach with a causal design. Data were obtained from 121 AZKO consumer respondents and analysed using multiple linear regression. The research results show that renaming and relaunching partially have a positive and significant effect on purchasing decisions. However, repositioning and redesign do not have a significant effect on purchasing decisions. Meanwhile, simultaneously, the four variables have a significant effect on purchasing decisions with an Adjusted R Square value of 0.586. These findings indicate that an increase in consumer understanding of the rebranding processes undertaken is an important factor in enhancing the purchasing decisions of AZKO consumers in Palembang City.